Consumo de álcool e outras drogas entre adolescentes da zona rural - Martins, Maria Margarete Brito (2018)
Adolescence is a healthy period in the life cycle and also a crucial stage for individuals in terms of habit formation, behavior patterns and socialization. In this period the individual is more vulnerable, and among these vulnerabilities the approach to alcohol and other drugs. Many studies deal with the use of alcohol and other drugs per adolescent in large centers, however, there is a need for a directed look at the children and youth population in rural areas, since the adolescents who live in these areas, for the most part, have less access to information. This is a qualitative study, based on the presuppositions of action research that aimed to implant the Adolescent Health Program in a Family Health Unit in the city of Serra Preta-BA. The study was carried out in a primary school of the municipal basic network and in the Family Health Unit of Bravo, eleven health professionals participated in that school; six professionals from the João Paulo I school, and 15 adolescents between the ages of 14 and 18, of both sexes, enrolled in school and enrolled in the Unit. Data were collected through focal group techniques and simple observation and analyzed by the Content Analysis technique proposed by Bardin. Ethical aspects were observed through Resolution 466/2012. The results are presented in two scientific papers: the first presents an experience report on the use of the Charles Maguerez Arch during data collection, entitled Working on prevention of alcohol and other drug use by adolescents through the arch of Charles Maguerez and the second article presents the results obtained through the research carried out with the adolescents entitled The consumption of alcohol and other drugs from the perspective of adolescents living in rural areas. The products resulting from this work were: (re) organization of the health professionals 'agenda, implementation of the flow chart and the training of the health team that helped transform the professionals' perspective on adolescent care and, finally, the intervention , entitled Adolescer com Saúde, mobilizing the school community, health team and other professionals engaged in the struggle to transform reality and the creation of an educational booklet for health and education professionals.